2022
DOI: 10.3390/ma15155372
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Gamma Irradiation on the Properties of Magnesium-Doped Hydroxyapatite in Chitosan Matrix

Abstract: This is the first report regarding the effect of gamma irradiation on chitosan-coated magnesium-doped hydroxyapatite (xMg = 0.1; 10 MgHApCh) layers prepared by the spin-coating process. The stability of the resulting 10 MgHApCh gel suspension used to obtain the layers has been shown by ultrasound measurements. The presence of magnesium and the effect of the irradiation process on the studied samples were shown by X-ray photoelectron spectroscopy (XPS). The XPS results obtained for irradiated 10 MgHApCh layers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 69 publications
4
16
0
Order By: Relevance
“…The large maxima noticed (for all the studied samples) at about 3450 cm −1 are specific to the hydroxyl vibration from HA. For the ZnHACh and ZnHAChT samples, the broad maxima specific to the chitosan (N-H vibration) and hydroxyapatite (O-H vibrations) observed between 3300 and 3600 cm −1 are overlapped [41].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The large maxima noticed (for all the studied samples) at about 3450 cm −1 are specific to the hydroxyl vibration from HA. For the ZnHACh and ZnHAChT samples, the broad maxima specific to the chitosan (N-H vibration) and hydroxyapatite (O-H vibrations) observed between 3300 and 3600 cm −1 are overlapped [41].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, for a more compressive study of the molecular structure of obtained samples, the second derivative spectra were achieved in the conditions described elsewhere [41]. The red lines from Figure 6 represent the second derivative spectra of ZnHA, ZnHACh and ZnHAChT samples.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, similar results regarding the physico-chemical characteristics of magnesium-doped hydroxyapatite/chitosan coatings obtained by rf magnetron sputtering discharge have been reported by B. Bita and collaborators [ 57 ]. In the study conducted by D. Predoi and coworkers [ 31 ] the strong antifungal activity of chitosan-coated magnesium-doped hydroxyapatite (x Mg = 0.1) layers obtained by spin-coating was proved against C. albicans fungal strain. At the same time, previous studies have demonstrated that the surface morphology and optical properties of chitosan-hydroxyapatite coatings obtained by rf magnetron sputtering discharge are influenced by the Ar gas working pressure [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of magnesium-doped hydroxyapatite in a chitosan matrix (Ca 10 −x Mg x (PO 4 ) 6 (OH) 2 ; x Mg = 0, 0.08 and 0.3) was conducted following our previous studies [ 25 , 31 ]. For this purpose, the value used for the Ca/P molar ratio was 1.67.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation